Destroy Your Enemy Becoming Your Friend - Arturo Sánchez Sanz (Clotho)
The legend of the battle of Troy between the hero Achilles and the Amazon queen Penthesilea is one of the most famous stories in Greek mythology. However, we may wonder why the Amazons decided to travel to Troy and become allies of King Priam to fight the Achaeans. This fact is important, especially since this episode does not appear in Homer’s work, but the author does mention the Amazons on three occasions. In one of them, King Priam himself is the protagonist, in his youth. Many years before the Achaeans besieged his city, the young Priam traveled to Phrygia, where he decided to accompany the rulers Otreus and Mygdon on their campaign towards the river Sangarius. There, they were surprised by a group of Amazons who did not hesitate to attack them – for no apparent reason. This paper analyzes both episodes’ written and archaeological sources to explain why the Amazons decided to change their minds and become Priam’s allies after having fought against the Trojan ruler years before. It analyzes the motives of Queen Penthesilea to confront the Achaeans, which would result in her death at the hands of the hero Achilles, who was in love with her.